2012
DOI: 10.3109/0284186x.2012.718444
|View full text |Cite
|
Sign up to set email alerts
|

Both macrophages and hypoxia play critical role in regulating invasion of gastric cancer in vitro

Abstract: Both macrophages and hypoxia play an indispensable role in regulating the invasion of gastric cancer cells in vitro; ADAMs, MMP9 and TIMP3 might be involved in TAM induced invasive power of gastric cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…While ADAM9 is regulated at the transcriptional level in monocytes and macrophages (3,10,55), ADAM9 is not regulated at the mRNA level in mature PMNs. ADAM9 is likely transcribed by PMN precursors in the bone marrow and stored as a performed proteinase within PMN granules and vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…While ADAM9 is regulated at the transcriptional level in monocytes and macrophages (3,10,55), ADAM9 is not regulated at the mRNA level in mature PMNs. ADAM9 is likely transcribed by PMN precursors in the bone marrow and stored as a performed proteinase within PMN granules and vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Another group looked at the role of tumor-associated macrophages (TAMs) in gastric cancer using a 3D dynamic migration imaging system to directly visualize the motility of tumor cells under normal and hypoxic conditions, both alone and in coculture with macrophages. They found that tumor cells in 3D culture (i) exhibit reduced migration speeds when under hypoxia; (ii) show increased migration rates when cocultured with macrophages; and most surprisingly; (iii) show a variable response when cocultured with macrophages under hypoxia where the migration speed of some cell lines increase under hypoxic conditions, while others decrease [32]. These apparently conflicting data emphasize that in vitro models do not converge on a set of coherent conclusions, suggesting that the phenotypes observed in vitro may be more a property of the model than the functions these cells actually exhibit in vivo and ultimate validation of any conclusion obtained from these in vitro assays must come from the ability to observe cell phenotypes, in vivo .…”
Section: Hypoxia Motility and Directionality In The Primary Tumormentioning
confidence: 99%
“…Importantly, comparison of the speeds reported in the few in vitro assays that measured this parameter [22,26,27,32,39,40] reveals that in vitro assays only recapitulate the slow migratory phenotype (Table 1). While treatment of the cells in culture to hypoxic conditions in some studies does result in an increase in migration rates, these elevated speeds still fall well within the slow migratory phenotype [35].…”
Section: Hypoxia Motility and Directionality In The Primary Tumormentioning
confidence: 99%
“…relatives (Qiu et al 2012;Cai et al 2013). With regard to ADAM9, previous study has showed that the mRNA and protein expression levels of this gene are elevated by the 14 regulation of reactive oxygen species under hypoxic stress conditions in prostate cancer cells (Shen et al 2013). In addition, hypoxia (1% oxygen) can also induce the 16 expression of ADAM9 in gastric cancer cells (Kim et al 2014).…”
Section: Signatures Of Deleterious Variation and Positive Selectionmentioning
confidence: 99%